Marché européen des margarines et des matières grasses à tartiner - Herreman Inneke (Oléagineux, Corps gras, Lipides, 2005)
IMACE, the International Margarine Association of the Countries of Europe represents 21 national associations of the margarine industry. While in 2003 the World Production increased to 10.1 Mt (9.3 Mt in 1998), the production of the European countries of 15 was 1.9 Mt (2.3 Mt in 1998). In 2003 the most important European producing countries are Germany (446,000 t), the United Kingdom (322,000 t), Belgium (268,000 t), the Netherlands (289,000 t) and Poland (510,000 t). The changes in food habits involved a decline of consumption. But the sector has invested a lot in optimizing the composition of its products, with a special attention for unsaturated fatty acids. European Union food legislation that has a particular impact on the margarine industry are the proposed EU Claims regulation, the proposed EU harmonization of vitamins and minerals, the EU directives on full ingredient labelling and on nutrition labelling. But the industry also actively pursues a road of self-regulation i.e. IMACE Code of Practice on Nutrition Claims, IMACE Code of Practice on Addition of Vitamins, IMACE Code of Practice on TFA. Several scientific publications recognize the margarine industry’s efforts in reducing TFA and underline that they are known as a determinant factor in the overall reduction of TFA in food products.